The Role of Marketing Skills for Local Products and Entrepreneurial Innovation in SME Performance - Putri Kencana, Yunita; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic development, yet many still face challenges in improving their performance lately in three years. This study aims to analyze the influence of entrepreneurial marketing, innovation capability, and purchase decision on the performance of MSMEs, with a case study on the local bag product brand Jims Honey in the Jabodetabek area. A quantitative approach was used, employing a survey method with 100 MSME respondents. Data were analyzed using SmartPLS 4.0 through Partial Least Squares (PLS) and Structural Equation Modeling (SEM) for testing hypotheses 1 to 4, and multiple linear regression for hypothesis 5. The results show that entrepreneurial marketing and purchase decisions have a positive and significant effect on MSME performance. In contrast, innovation capability has a negative and significant effect. Among the three variables, the purchase decision has the most dominant influence. Simultaneously, all three variables significantly affect MSME performance. The study concludes that MSME success is more strongly influenced by effective marketing strategies and consumer trust, while innovative efforts need to be more aligned with market needs. The findings suggest that MSME owners should refine their promotional strategies, enhance service quality, and implement targeted innovation to achieve improved business performance.